2008
DOI: 10.1161/circulationaha.107.733329
|View full text |Cite
|
Sign up to set email alerts
|

Acute Administration of Fish Oil Inhibits Triggered Activity in Isolated Myocytes From Rabbits and Patients With Heart Failure

Abstract: Background-Fish oil reduces sudden death in patients with prior myocardial infarction. Sudden death in heart failure may be due to triggered activity based on disturbed calcium handling. We hypothesized that superfusion with 3-polyunsaturated fatty acids (3-PUFAs) from fish inhibits triggered activity in heart failure. Methods and Results-Ventricular myocytes were isolated from explanted hearts of rabbits with volume-and pressure-overload-induced heart failure and of patients with end-stage heart failure. Memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
59
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 37 publications
4
59
1
Order By: Relevance
“…11,20,21 This fatty acid is associated with a reduced response of myocytes to noradrenaline, which plays an important role in worsening CHF as a neurohormonal response. 16 The effect of omega-3 was attributed to its ability to lower intracellular calcium and inhibit myocyte activity. Several trials have demonstrated the antiarrhythmic properties of omega-3 PUFA in patients with a history of myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…11,20,21 This fatty acid is associated with a reduced response of myocytes to noradrenaline, which plays an important role in worsening CHF as a neurohormonal response. 16 The effect of omega-3 was attributed to its ability to lower intracellular calcium and inhibit myocyte activity. Several trials have demonstrated the antiarrhythmic properties of omega-3 PUFA in patients with a history of myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 It has now become apparent that persistent I Na plays an important role in the genesis of ischemia-induced ventricular damages and also in arrhythmias observed in failing hearts and that persistent I Na represents an attractive target to focus on to provide protection from Na ϩ -induced Ca 2ϩ overload. We previously reported 5 that DHA and EPA, in a same range of concentration used in the study by den Ruijter et al, 1 concentration-dependently reduced the persistent I Na artificially induced with veratridine, as well as the one involved in LQT3 syndrome.…”
Section: To the Editormentioning
confidence: 64%
“…We read with a great interest the article by den Ruijter et al, 1 which showed that acute application of 3-polyunsaturated fatty acids (DHA and EPA) reduced action potential duration and decreased diastolic and systolic intracellular calcium in myocytes from pathological hearts explanted from rabbits and humans. Consequently, 3-polyunsaturated fatty acids abolished triggered activity and reduced the number of delayed afterdepolarizations and calcium levels after transients.…”
Section: To the Editormentioning
confidence: 99%
“…1 In their letter, Drs Pignier and LeGrand express their belief that inhibition of the persistent component of the sodium current (I Na,P ) constitutes a key mechanism of the antiarrhythmic properties of 3-polyunsaturated fatty acids in heart failure in our study, 1 a factor not mentioned by us. We agree that persistent I Na,P , if present, may contribute to Ca 2ϩ overload-induced arrhythmogenesis in heart failure.…”
mentioning
confidence: 66%
“…2 We cannot exclude I Na,P in human myocytes, although similarity of the response to 3-polyunsaturated fatty acids makes species differences less probable. In addition, reductions in [Ca 2ϩ ] i levels after application of 3-polyunsaturated fatty acids have been observed in isolated myocytes from both healthy and diseased hearts 1,3,4 and are therefore likely independent of I Na,P .…”
mentioning
confidence: 99%